Study of Discrete Characteristics of Signatures Inks and Photography for Forensic Investigation: Differentiation of documents created by laser printers, inkjet printers, and electrostatic copiers for forensic investigation (Journal of Advances and Scholarly Researches in Allied Education, 2019)
His paper describes a method by which laser printers, inkjet printers, and electrostatic copiers, three widely used document production devices, may distinguish documents created. Based on characteristics extracted from the characters in the documents, the proposed approach will differentiate between documents provided by these sources. It can therefore also be used to detect manipulated documents produced by a mixture of these sources. The features associated with laserinkjet printers and electrostatic copiers are analyzed and the signatures produced by the various physical and technical processes involved in each type of printing are determined. We computed the features of noise energy, contour roughness, and average gradient on the basis of the study of these signatures. This is the first work to differentiate documents created by a laser printer, inkjet printer and copier, to the best of our knowledge, on the basis of features drawn from individual characters in the documents. Experimental findings suggest that this technique has an average precision of 90 percent and works with JPEG compression.